Hydrazine carbodithioic acid pyridinium-2-yl methyl ester chloride. - Crouse, Karen Anne; Kar , Teng Chew; Yamin, Bohari M.; Seik, Weng Ng; Tarafder, M.T.H. (International Union of Crystallography, 2003)
The title compound, [C7H10N3S2]+·Cl-, exists as an ionic compound of a dithiocarbazate system, with a zwitterionic +H3NNCS- moiety and a protonated pyridine ring. The C-S thione bond distance of the zwitterionic moiety [1.708 (2) Å] is longer than the normal double bond and the C-N of the carbazate moiety has double-bond character. The crystal packing is stabilized by intramolecular hydrogen bonds, which form a two-dimensional network perpendicular to b.